Species occurrence of ticks in South America, and interactions with biotic and abiotic traits - Estrada-Peña, Agustín; Nava, Santiago; Tarragona, Evelina Luisa; Bermúdez, Sergio; de la Fuente, José; Domingos, Ana; Labruna, Marcelo B.; Mosqueda, Juan; Merino, Octavio; Szabó, Matías P.J.; Venzal, José Manuel; Guglielmone, Alberto (Springer Nature, 2020)
The datasets of records of the distribution of ticks and their hosts are invaluable tools to understand the phylogenetic patterns of evolution of ticks and the abiotic traits to which they are associated. Such datasets require an exhaustive collection of bibliographical references. In most cases, it is necessary the confirmation of reliable identification of ticks, together with an update of the scientific names of the vertebrate hosts. These data are not easily available, because many records were published in the socalled “grey literature”. Herein, we introduced the Dataset of Ticks in South America, a repository that collates data on 4,764 records of ticks (4,124 geo-referenced) with a special reference to an extra 2,370 records of ticks on cattle, together with a set of abiotic traits, curated from satellite-derived information over the complete target region. The dataset includes details of the phylogenetic relationships of the species of hosts, providing researchers with both biotic and abiotic traits that drive the distribution and evolution of ticks in South America.